Measuring dimensions of technology resistance and managers’ performance using structural equation modelling and TECHPROVED system / Norzaidi Mohd Daud, Intan Salwani Mohamed, Rashid Alhamali - Mohd Daud, Norzaidi; Mohamed, Intan Salwani; Alhamali, Rashid (2012)
This article examines the impact of technology resistance (i.e. co-workers affluence, negative prior experience, efficacy experience, poor systems design and loss of power) on manager‟s performance in Malaysia maritime industry. The structural equation modelling (SEM) results indicate that all factors are negatively influence managers‟ performance. This is probably the first that investigate technology resistance and managers‟ performance using SEM and TECHRPOVED system. The results provide insights on how the Malaysian maritime industry could improve upon their intranet adoption.